Unraveling the Legal Labyrinth: An In-depth Review of Domestic Violence Regulation in Indonesia - Rohaya, Nizla; Suartini; Mohammad; Prosper Maguchu; Gufroni (Nurani, 2024)
Domestic violence cases continue to increase every year, due to factors such as economic problems, fatigue due to traffic congestion, increasing life demands, and many other factors. Nowadays, news about domestic violence incidents is increasingly common. To date, Indonesia has four laws and regulations governing domestic violence. However, the existence of these four laws and regulations has created a new problem, namely over-regulation or excessive regulation which has caused several negative impacts which are the subject of discussion in this paper.   The research method used in this research is qualitative through normative legal research. The data obtained is analyzed using a conceptual approach to understand the concept of domestic violence in four different laws and regulations in Indonesia. This research focuses on the harmony of norms and ideas of domestic violence in Indonesian law. The purpose of this research is to find a conception to simplify the regulations governing domestic violence in Indonesia by unifying the four regulations above. Based on the results and discussion, the author provides recommendations in terms of streamlining regulations related to domestic violence.  Simplification of regulations is needed to help reduce barriers in handling domestic violence, increase protection for victims, and support prevention efforts. Therefore, it is important to involve stakeholders, legal experts, human rights activists, and other communities in designing changes to domestic violence laws to make them more effective.